Folkcommunication: The micropolitical actions established in the use of audiovisual in theartistic interventions "The Giant Step"in a Makuxicommunity of Roraima (Revista Internacional de Folkcomunicação, 2019)
In this article we seek to understand the articulation of Folkcommunication in the artistic interventions of global reach and how they reterritorialize the artistic development in the indigenous communities. To this end, we are accompanying the third edition of the artistic intervention "The Giant Step" conceived by the Hungarian-Swiss artist Viliam Mauritz in the indigenous community Raposa I, belonging to the indigenous land Raposa Serra do Sol / RR. The realization of "The Giant Step" in the Amazon was a proposal of the idealizer when meeting the indigenous artist Makuxi Jaider Esbell. From this meeting, we analyze the different micropolitical forces lines (GUATTARI & ROLNIK, 2013), that is, how dominant subjectivation modes can (or may not) be subverted. In this problematization, we perceive the articulation of the audiovisual as an articulating and potentiating element of Folkcommunication. It establishes an articulation of the artistic interventions with the indigenous culture deterritorializing the circuits of the contemporary art in the moment in which it enhances the reach from the digital media. Folkcommunication; Artistic interventions; Makuxi Indian; Micropolitics; Audio-visual.